Oportunidades de mobilidade e cooperação científica Brasil – Alemanha - Sartori, Nina (2024)
Facts and Figures German Research System. Approx. 1,100 publicly funded research institutions Expenditure on R&D: €113bn = 3.14% of GDP → 67% coming from industry 750,000 staff in R&D More than 35,000 university collaborations with 164 countries → around 650 university agreements between Brasil and German